Histology of the Androgenic Gland and Expression of the Insulin-like Androgenic Gland Hormone Precursor Gene in the Genital Organ of Pacific White Shrimp Litopenaeus vannamei. Issue 3 (1st May 2014) - Vázquez-Islas, Grecia; Garza-Torres, Rodolfo; Guerrero-Tortolero, Danitzia A.; Campos-Ramos, Rafael
Abstract: The location of the androgenic gland in the genital organ in male Pacific white shrimp Litopenaeus vannamei (Boone, 1931 ) was analyzed by histology and expression of the insulin-like androgenic gland hormone precursor gene (Lv-IAG). The androgenic gland in L. vannamei is a group of three conspicuous semicircular cellular masses interconnected by cord-like androgenic gland cells, in parallel and attached to the distal vas deferens and terminal ampoule, which form a hook-like morphology. Lv-IAG expression occurs mainly at the terminal ampoule, but also at the distal part of the descending medium vas deferens and the narrow distal vas deferens. These specific regions of Lv-IAG expression basically match the anatomical localization of the androgenic gland observed by histology. The complete cDNA nucleotide sequence of Lv-IAG precursor had 87% to Fenneropenaeus chinensis (Osbeck, 1765 ), 84% identity to Penaeus monodon Fabricius, 1798 (Pm-IAG), and 82% to Marsupenaeus japonicus (Bate, 1888 ) (Maj-IAG). The deduced encoding sequence from an open reading frame of 507 bp contained a signal peptide, a B chain, a C peptide, and an A chain that correspond to the androgenic gland insulin-like hormone polypeptide in decapods, where six highly conserved cysteine residues of the A and B chains fold the mature peptide through disulfide bridges. The amino-acid sequence showed high identity to P. monodon (80%), F. chinensis (80%), and M. japonicus (72%), whereas the match to other decapod families Palaemonidae, Parastacidae, and Portunidae was low (24-32%). This study extends our knowledge of the molecular structure of insulin-like peptides related to sex differentiation in malacostraca.